Effects of compression on water distribution in gas diffusion layer materials of PEMFC in a point injection device by means of synchrotron X-ray imaging - Ince, Utku U.; Markötter, Henning; George, Michael G.; Liu, Hang; Ge, Nan; Lee, Jongmin; Alrwashdeh, Saad S.; Zeis, Roswitha; Messerschmidt, Matthias; Scholta, Joachim; Bazylak, Aimy; Manke, Ingo (International Journal of Hydrogen Energy, 2018)
In this study, ex-situ experiments performed with a point injection device are conducted to evaluate water distributions in gas diffusion layer (GDL) materials which serve as porous transport media in polymer electrolyte membrane fuel cells (PEMFCs). In this regard, GDL samples manufactured by SGL Group are placed into the point injection device and visualized by means of synchrotron X-ray radiographic and tomographic imaging. The resulting image data undergoes a coordinate transformation that ascertains water agglomerations in GDL pores with regard to their radial displacements from the injection point. In this way, water transport in two different GDL samples possessing the same structural characteristics, but with unique compression rates, are investigated in terms of in-plane water distribution. The radial displacement analysis indicated that the pore saturation of the compressed GDL is higher in both the micro porous layer (MPL) region and the carbon fiber substrate region than that of the uncompressed GDL. The water agglomerations in the uncompressed GDL are predominantly observed in the vicinity of the injection point, indicating a limited in-plane transport. Conversely, in the compressed case water accumulations are detected far from the injection point, even at the edge of the GDL, pointing out that compression promotes the in-plane transport. Prior to the ex-situ experiments, both GDL samples have undergone an ageing procedure to mimic realistic cell operating conditions.
CRIS-Team Scopus Importer:2023-08-01
Keywords: GDL materials; In-plane water transport; Polymer electrolyte membrane fuel cell; Synchrotron X-ray imaging; Tortuosity; Water management